2023
DOI: 10.1021/acsami.2c20905
|View full text |Cite
|
Sign up to set email alerts
|

Diode Characteristics in Magnetic Domain Wall Devices via Geometrical Pinning for Neuromorphic Computing

Abstract: Neuromorphic computing (NC) is considered a potential vehicle for implementing energy-efficient artificial intelligence. To realize NC, several technologies are being investigated. Among them, the spin–orbit torque (SOT)-driven domain wall (DW) devices are one of the potential candidates. Researchers have proposed different device designs to achieve neurons and synapses, the building blocks of NC. However, the experimental realization of DW device-based NC is only at the primeval stage. Here, we have studied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We are exploring complementary concepts to achieve symmetric bidirectional motion without an applied magnetic field. 83 Synaptic Device Investigations. The realization of synaptic functions in DW devices requires multiresistance states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are exploring complementary concepts to achieve symmetric bidirectional motion without an applied magnetic field. 83 Synaptic Device Investigations. The realization of synaptic functions in DW devices requires multiresistance states.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pinning strength of the pinning sites of this kind may not be strong enough to support synaptic functionalities. More recently, Rahaman et al studied the concepts of the pine tree DW devices to pin the DWs at the junction of the two DW device segments 83 and demonstrated the intermediate magnetization states.…”
Section: Resultsmentioning
confidence: 99%
“…Pinning the domain wall for an extended period in a uniform pillar devoid of structural disturbances poses challenges. Fortunately, structures such as those with periodically varying pillar diameter or multilayer films with and without perpendicular magnetic anisotropy layers have been proposed to enable domain wall pinning [18,19,37]. In actually fabricated pillars, unintentionally created defects could act as pinning sites for domain wall motion.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, Rahaman et al investigated pine-tree-shaped DW devices for achieving the synaptic functionalities by exploiting Laplace force on elastic DWs. [52] Multiple magnetization states have been demonstrated by moving the DW along the device via SOT. Cai et al demonstrated multilevel resistance states by pinning the DW at different positions defined by the width changes of the structure.…”
Section: Magnetic Dw Devicesmentioning
confidence: 99%